USO DE RESÍDUO INDUSTRIAL E TABACO NA COMPOSIÇÃO DE SUBSTRATOS PARA PRODUÇÃO DE MUDAS DE TOMATE CEREJA - SCHWARTZ, Phillip Silva; LOVERA, Carlos Alberto; SANTOS, Benajmin Abel dos; GOTTARDI, Gabriel Alves; PESTANA, Carlos Eduardo Skittberg; ZOZ, Tiago (ANAIS DO ENIC, 2025)
-